513 CD26 enzymatic activity modulates efficient migration of adoptively transferred T cells to solid tumors. (10th December 2020) - Wyatt, Megan; Bailey, Stefanie; Nelson, Michelle; Knochelmann, Hannah; Smith, Aubrey; RIvera, Guillermo Rangel; Reyes, Amalia Rivera; Paulos, Chrystal
Abstract : Background: The inadequate ability of adoptively transferred T cells to eradicate solid tumors limits their use in treatments for patients afflicted with those cancers. Efforts to improve ACT for solid tumors aim to identify strategies that poise T cells for optimal response. We have previously identified a specific subset of CD4 T cells which express high levels of the ubiquitous ectoenzyme dipeptidyl peptidase-4 (DPP-4), also known as CD26, that produce a tremendous antitumor response in solid tumor models. We therefore sought to investigate the importance of CD26 on T cells destined for ACT. Methods: We adoptively transferred tumor specific CD26 + T cells into melanoma tumor-bearing CD26 -/- mice, and continuously blocked the CD26 enzymatic activity of the donor cells in vivo with sitagliptin, an established competitive inhibitor of CD26. Results: Tumors in sitagliptin-treated mice eventually reached study endpoint, while tumors untreated mice were regressed for 130+ days. Tumor infiltration of donor cells and host CD8 and CD4 cells was diminished with sitagliptin treatment. A 32-plex cytokine array of blood plasma revealed a diminished profile of cytokines and chemokines, indicating that the inflammatory response of the T cells was dampened with sitagliptin treatment. Further experiments characterized the ability of CD26 + T cells to respond to tumor trafficking signals with a transwell migration assay and found that sitagliptin treatment significantly impaired their migratory capacity. However, sitagliptin did not impair the ability of T cells to functionally respond to antigen. Conclusions: These data suggest that the enzymatic activity of CD26 is important for the ability of T cells to migrate to the tumor site in order to mount an effective antitumor response. Further investigations into the mechanism behind the role of CD26 are ongoing. Ethics Approval: This study was approved by the Medical University of South Carolina's IACUC, protocol #00488